Classification of tourism business certification institution auditors based on the decision tree algorithm C4.5: case study of LSUP XYZ - Ni Wayan Rena Mariani; I Made Sudjana (Jurnal Mantik, 2023)
Auditors who have appropriate competence are needed to carry out certification. The amount of experience a person has before becoming an Auditor determines the competence possessed by an Auditor. To be assigned to carry out certification, an auditor needs special competencies such as areas of expertise, work experience, and the Schemes and Standards that become the reference for certification. Auditors owned by LSUP need to be classified so that they can be assigned according to their competence. The C4.5 Decision tree algorithm is one of the methods that can be used to create a model used to classify and predict auditor competence. 65 data from 221 data are used as training data to form a model in the form of a tree structure. This model consists of 3 attributes that form a Node in a tree structure, namely the Workplace, Skill and Standard attributes. Each attribute has a value that forms a branch. The model was evaluated using the Confusion Matrix with a matrix size of 7x7 which resulted in a TP value of 99, FP value of 121, FN value of 121, and TN value of 1199. The accuracy level of this model is quite good, namely 84%. But the Precise and Recall values are not very good, only 45%.